Pengembangan Pertanian Organik di Indonesia - Henny Mayrowani (Forum penelitian Agro Ekonomi, 2012)
EnglishAwareness of the dangers posed by the use of synthetic chemicals in farming attracts attention at both the producers and consumers. Most consumers will choose safe food ingredients for better health and it drives increased demand for organic products. Healthy, environmentally friendly life-style becomes a new trend and has been institutionalized internationally which requires assurance that agricultural products should be safe for consumption (food safety attributes), high nutrient content (nutritional attributes) and environmentally friendly (eco-labeling attributes).  Indonesia has a great potential to compete in the international market, but it should be implemented gradually. This is because of many comparative advantages, i.e. (i) there are large land areas available for organic  farming; (ii) technology to support organic farming is available such as composting, no-tillage planting, biological pesticides, among others. Although the government has launched various policies on organic agriculture such as "Go Organic 2010”, but the development of organic farming in the country is relatively slow. This situation is due to various problems such as market constraints, consumers’ interest, relatively expensive organic products certification for small farmers, and lack of farmers’ partnership with private companies. However, interest for organic farming has grown and it is expected to have positive impacts on the development of organic agriculture in Indonesia. IndonesianKesadaran tentang bahaya yang ditimbulkan oleh pemakaian bahan kimia sintetis dalam pertanian menjadikan pertanian organik menarik perhatian baik di tingkat produsen maupun konsumen. Kebanyakan konsumen akan memilih bahan pangan yang aman bagi kesehatan dan ramah lingkungan, sehingga mendorong meningkatnya permintaan produk organik. Pola hidup sehat yang akrab lingkungan telah menjadi trend baru  dan telah melembaga secara internasional yang mensyaratkan jaminan bahwa produk pertanian harus beratribut aman dikonsumsi (food safety attributes), kandungan nutrisi tinggi (nutritional attributes), dan ramah lingkungan (eco-labelling attributes). Indonesia memiliki potensi yang cukup besar untuk bersaing di pasar internasional walaupun secara bertahap. Hal ini karena berbagai keunggulan komparatif antara lain: (i) masih banyak sumberdaya lahan yang dapat dibuka untuk mengembangkan sistem pertanian organik, (ii) teknologi untuk mendukung pertanian organik sudah cukup tersedia seperti pembuatan kompos, tanam tanpa olah tanah, pestisida hayati dan lain-lain. Walaupun pemerintah telah mencanangkan berbagai kebijakan dalam pengembangan pertanian organik seperti ‘Go Organic 2010’, namun perkembangan pertanian organik di Indonesia masih sangat lambat.  Keadaan ini disebabkan oleh berbagai kendala antara lain kendala pasar, minat konsumen dan pemahaman terhadap produk organik, proses sertifikasi yang dianggap berat oleh petani kecil, organisasi petani serta kemitraan petani dengan pengusaha. Namun minat bertani terhadap pertanian organik sudah tumbuh. Hal ini diharapkan akan berdampak positif terhadap pengembangan petanian organik.